The Readiness Of Ips Teachers In Facing The Change In The Kurikulum Merdeka At Smp Negeri 1 Martapura - Astuti, Kartika Novi; Mutiani, Mutiani; Sari, Raihanah; Syarifuddin, Syarifuddin; Rahmia, Sovia Husni (The Kalimantan Social Studies Journal, 2024)
The ‘Merdeka Belajar’ learning system is a form of new policy in updating the previous curriculum or what is known as the 2013 Curriculum and in implementing it, of course, it requires careful preparation so that the obstacles that arise can be overcome properly. This study aims to determine the readiness of social studies teachers at SMP Negeri 1 Martapura in implementing independent learning. Data for this type of research was collected through documentation, interviews and observations. The results show that teachers at SMP Negeri 1 Martapura are ready to implement an independent curriculum. This research uses teachers' cognitive, physical and psychological readiness as an indication of their readiness level. Teachers' cognitive, physical and psychological readiness are indicative of the level of readiness.